The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1093/infdis/jix666
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Inflammation but Not in T-Cell Activation Precede Non-AIDS-Defining Events in a Case-Control Study of Patients on Long-term Antiretroviral Therapy

Abstract: NCT00001137.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…If on-treatment inflammation does predict future events in this region, our data support a potentially similar benefit of ART in both earlier- and late-stage disease treatment initiators who survive and attain virologic suppression. There are suggestions from Western settings that levels of inflammation after ART initiation are potentially more predictive of future complications than pretreatment levels [13]. Similarly, our group previously reported that changes in sCD14 and the ratio of kynurenine to tryptophan (KT ratio) 6 months after treatment, but not before treatment, were predictive of increased carotid intima media thickness years later in Uganda [9] and that higher levels of KT ratio, sCD14, IL-6 and D-dimer were associated with a greater risk of mortality 6 months after ART initiation [14].…”
Section: Discussionmentioning
confidence: 99%
“…If on-treatment inflammation does predict future events in this region, our data support a potentially similar benefit of ART in both earlier- and late-stage disease treatment initiators who survive and attain virologic suppression. There are suggestions from Western settings that levels of inflammation after ART initiation are potentially more predictive of future complications than pretreatment levels [13]. Similarly, our group previously reported that changes in sCD14 and the ratio of kynurenine to tryptophan (KT ratio) 6 months after treatment, but not before treatment, were predictive of increased carotid intima media thickness years later in Uganda [9] and that higher levels of KT ratio, sCD14, IL-6 and D-dimer were associated with a greater risk of mortality 6 months after ART initiation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IL‐6 levels have been associated with arteriosclerosis and, in addition to hs‐CRP and d ‐dimer, with a higher risk of cardiovascular disease . Also, elevated IL‐6 and sCD14 levels were independently associated with an increased risk of mortality and changes in these biomarkers could be predictive of the emergence of non‐AIDS‐related events . In contrast, a reduction in IL‐6 and d ‐dimer levels by 25% was found to result in a 37% reduction in the rate of serious non‐AIDS‐related events/deaths .…”
Section: Discussionmentioning
confidence: 99%
“…85 In longitudinal studies, rising levels of these biomarkers better predicted the development of NADIs than a single value at recruitment. 86 These findings suggest that impaired gut barrier function leads to the translocation of microbial products from the gut into the circulation, where they activate monocytes and macrophages, initiating a cycle of chronic inflammation. 85 This appears to be related to the activation of a specific subset of inflammatory monocytes which express Tissue Factor: these can secrete high levels of pro-inflammatory cytokines as well as trigger the coagulation cascade, so are particularly implicated in HIV-associated coagulopathy.…”
Section: Pathogenesis Of Chronic Co-morbiditiesmentioning
confidence: 99%